Paediatric Imaging Manual - Tröger, Jochen; Seidensticker, Peter (Springer Medizin Verlag Heidelberg, 2008)
Compared to adults, children and adolescents suffer from different diseases and require different treatments. The same is true where imaging is concerned. The diagnostic strategies are different. The care prior to, during, and following the examination also differs from that of adults. This CME accredited Manual provides a comprehensive overview on the field of paediatric radiology and suggests imaging strategies for the most common clinical indications in children and adolescents.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Bildgebendes Verfahren; Krankheit; Kind